Does Fiscal Decentralization Promote or Inhibit the Improvement of Carbon Productivity? Empirical Analysis Based on China’s Data - Feng, Guo; Shulian, Xue; Renjin, Sun (Frontiers in Environmental Science, 2022)
Based on the panel data of 30 provinces in China from 2010 to 2019, this paper empirically analyzes the relationship between fiscal decentralization and carbon productivity using spatial econometric model, and calculates the direct effect, spatial spillover effect and total effect of fiscal revenue decentralization and fiscal expenditure decentralization on carbon productivity respectively through effect decomposition. The empirical results show that: (1) The spatial agglomeration effect of China’s provincial carbon productivity is obvious, which shows an upward trend. The heterogeneity of carbon productivity among different provinces is obvious. The overall performance is as follows: Eastern provinces > Central provinces > Western provinces. (2) Fiscal revenue decentralization and fiscal expenditure decentralization can significantly promote the improvement of carbon productivity. Fiscal expenditure decentralization plays a greater role in promoting carbon productivity than fiscal revenue decentralization. (3) Fiscal revenue decentralization and fiscal expenditure decentralization have significant positive direct effects and negative spatial spillover effects on the improvement of carbon productivity. Increasing fiscal decentralization is conducive to improving the carbon productivity of the province, but it will inhibit the carbon productivity of neighboring provinces. Finally, it puts forward policy suggestions to promote the improvement of carbon productivity from the perspective of fiscal decentralization.